Structure of Apatite Nanoparticles Derived from Marine Animal (Crab) Shells - Bhattacharjee, Birendra Nath; Mishra, Vijay Kumar; Rai, Shyam Bahadur; Parkash, Om; Kumar, Devendra (American Chemical Society, 2019)
In the present investigation, crab shells as seafood wastes were successfully recycled into an extremely useful biomaterial by the thermal treatment method. Thermogravimetric-differential thermal analysis studies concluded that the calcination temperature must be beyond 570 °C to get a fine and crystalline apatite powder from the crab shells. Thus, the calcination temperature is taken to be 700 °C. Powder X-ray diffraction analysis of the calcined crab shells revealed hydroxyapatite (HAp)/carbonated HAp (CHAp) with an average crystallite size of 24.4 nm. Scanning electron microscopy revealed the surface morphology of the crab shells-derived apatite powder as needle-like nanorods of HAp of diameter ≈ 100-300 nm and nanospheres of CHAp of diameter ≈ 100-500. Energy-dispersive X-ray spectroscopy showed the presence of calcium, phosphorous, magnesium, and oxygen as major elements in the apatite constituents. Fourier transform infrared as well as Raman spectroscopies confirmed the formation of apatite powder. X-ray photoelectron spectroscopy results indicated the electronic environment and oxidation states of the constituent elements, Ca, C, and P. On the basis of the results obtained from various characterization techniques, the overall study emphasized an environment-friendly and cost-effective approach for recycling of the bio-pollutant and synthesis of ultra-fine, ultra-crystalline apatite-based excellent biomaterial derived from crab shells as seafood wastes with its application as a futuristic biomaterial in bone/teeth implants
An Environment-Friendly and Cost-Effective Novel Approach to Recycle Seafood Waste
Keywords: Apatite Nanoparticles Derived; Marine Animal (Crab) Shells; Environment-Friendly; Cost-Effective; Novel Approach; Recycle Seafood Waste